2020
DOI: 10.1038/s41467-020-17860-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and enzymatic evidence of acetogenesis by anaerobic methanotrophic archaea

Abstract: Anaerobic oxidation of methane (AOM) mediated by anaerobic methanotrophic archaea (ANME) is the primary process that provides energy to cold seep ecosystems by converting methane into inorganic carbon. Notably, cold seep ecosystems are dominated by highly divergent heterotrophic microorganisms. The role of the AOM process in supporting heterotrophic population remains unknown. We investigate the acetogenic capacity of ANME-2a in a simulated cold seep ecosystem using high-pressure biotechnology, where both AOM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 84 publications
1
41
0
1
Order By: Relevance
“…We found apart from CH 4 , which acts as the key environmental variable shaping the bacterial community structure, DOC, nitrate, and ammonium concentrations also correlated statistically significantly with bacterial community abundances. Because CH 4 oxidation by autotrophic methanotrophs leads to DOC production (Yang et al, 2020), the effect of DOC on shaping the bacterial community may be caused by CH 4 variation. Moreover, as many oil-degrading bacteria are enriched at the LIS and HIS sites, there is also the possibility of oil seepage at these sites with DOC produced through oil biodegradation by these bacteria (Orcutt et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We found apart from CH 4 , which acts as the key environmental variable shaping the bacterial community structure, DOC, nitrate, and ammonium concentrations also correlated statistically significantly with bacterial community abundances. Because CH 4 oxidation by autotrophic methanotrophs leads to DOC production (Yang et al, 2020), the effect of DOC on shaping the bacterial community may be caused by CH 4 variation. Moreover, as many oil-degrading bacteria are enriched at the LIS and HIS sites, there is also the possibility of oil seepage at these sites with DOC produced through oil biodegradation by these bacteria (Orcutt et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…HHP may induce significant metabolic alterations within cells, as it alters the dissolved gas concentration and the intracellular oxidation status (Xie et al ., 2018; Yang et al ., 2020). The former impact is straightforward in that more gas is dissolved under elevated hydrostatic pressure.…”
Section: Figurementioning
confidence: 99%
“…Although the exact formation mechanism of methane-derived DOC is currently unclear, biochemical processes including methane-sourced carbon incorporation into acetate or larger biomoleculars, microbial excretion, and biomass degradation have been proposed (Hoehler et al, 1994;Yang et al, 2020). Here, greater amount of fluorescent protein-like components (C2 and C4) and correspondingly less amount of humic-like components (C1 and C3) at the seep cores (ROV1, ROV5) than those at the reference core (QDN-C-S03) suggests enhanced microbial activities and resulting release of more labile, proteinlike components at the seep cores (Figure 3).…”
Section: Enhanced Production Of Labile Dissolved Organic Carbon In the Seep Sedimentsmentioning
confidence: 99%
“…However, the correlation between the fluorescent intensity of the other protein-like component-C4 and DOC concentration as well as δ 13 C-DOC at both seep cores is less remarkable compared to C2, likely implying complicated sources and formation mechanism of C4. Although the specific chemical composition of methane-derived DOC has yet to be investigated, it has been suggested that methane could be converted to low-molecular-weight, labile organic materials (e.g., acetate) by AOM (Yang et al, 2020). This inference was demonstrated by the identification of a complete archaeal acetogenesis pathway in the ANME-2a genome and the activity of the key enzymes in acetate generation (Yang et al, 2020).…”
Section: Enhanced Production Of Labile Dissolved Organic Carbon In the Seep Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation